Synergistic effect between the KCNQ1 haplotype and alcohol consumption on the development of type 2 diabetes mellitus in Korean cohorts - Ji Young Park (Nature Portfolio, 2021)
Abstract Potassium voltage-gated channel subfamily Q member 1 (KCNQ1) is one of the strongest susceptibility genes for type 2 diabetes mellitus (T2DM). Association studies between KCNQ1 genetic variants and T2DM have been reported. The multifactorial disease T2DM is caused by interactions between genetic susceptibility and environmental factors. In this study, we examined the associations between the KCNQ1 haplotype, which consists of the major alleles rs3852528, rs11024175, and rs2237892 (ht: ACC), and environmental factors such as alcohol consumption, which are related to the risk of T2DM, in two independent Korean populations. Data from health examination studies, i.e., HEXA (n = 50,357 subjects) and the Ansung–Ansan community-based Korean cohort study (n = 7603), were analyzed. In both cohorts, fasting blood glucose levels were significantly increased in moderate-to-heavy drinkers and carriers of the homozygous ACC haplotype. A significant association between the KCNQ1 haplotype and alcohol consumption in the risk of diabetes was observed in the HEXA (OR 1.587; 95% CI 1.128–2.234) and Ansung–Ansan (OR 2.165; 95% CI 1.175–3.989) cohorts compared with abstainers not carrying the KCNQ1 haplotype. Associations of the KCNQ1 haplotype with alcohol consumption and β-cell function were observed in the Ansung–Ansan cohort. Moderate-to-heavy drinkers with the ACC haplotype had lower fasting insulin levels and mean 60 min insulinogenic index (IGI60) compared with light drinkers and abstainers not carrying the ACC haplotype. These findings indicate that KCNQ1 variants play a synergistic role with alcohol consumption in the development of T2DM and impaired β-cell function.